2024
DOI: 10.61678/bursamed.1390634
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge of Students at Bursa Faculty of Medicine towards Artificial Intelligence: A Survey Study

Deniz GÜVEN,
Elif Güler KAZANCI,
Ayşe ÖREN
et al.

Abstract: Objectives: Artificial intelligence (AI) is being increasingly widely employed in medicine. Various artificial intelligence software solutions will most certainly be available to medical students when they begin their jobs after completing school. The goal of this study was to assess medical faculty students' knowledge and attitudes about AI in medicine. Methods: In 2020-2021, students at the University of Health Sciences, Bursa Training and Research Hospital participated in an online survey using Google… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For instance, a multiple-group analysis of prospective German teachers revealed gender-specific factors that influence the acceptance of AI-based applications, underscoring the importance of addressing these aspects in educational settings [ 37 ]. Similarly, attitudes toward AI among medical and pharmacy students have shown variations that could affect future implementation and use in medical practice [ 38 , 39 ]. In the healthcare sector, a study among Chinese dermatologists indicated varying levels of engagement with AI, influenced by gender among other factors, which could impact the adoption and effective use of AI technologies in dermatology [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a multiple-group analysis of prospective German teachers revealed gender-specific factors that influence the acceptance of AI-based applications, underscoring the importance of addressing these aspects in educational settings [ 37 ]. Similarly, attitudes toward AI among medical and pharmacy students have shown variations that could affect future implementation and use in medical practice [ 38 , 39 ]. In the healthcare sector, a study among Chinese dermatologists indicated varying levels of engagement with AI, influenced by gender among other factors, which could impact the adoption and effective use of AI technologies in dermatology [ 40 ].…”
Section: Introductionmentioning
confidence: 99%